Konstruksi Kalimat pada Dialog Film Hafalan Shalat Delisa Karya Tere Liye - Stefany, Puronami Sarah; Sri Satyawati, Made; Putu Putra, Anak Agung (Stilistika : Journal of Indonesian Language and Literature; Vol 1 No 1 (2021)DO - 10.24843/STIL.2021.v01.i01.p01, 2021)
This research is entitled “Konstruksi Kalimat Pada Dialog Film Hafalan Shalat Delisa Karya Tere Liye”. This study aims to describe (a) the structure of the sentence and (b) what types of sentences are used in the dialogue. The data collection methods and techniques used are the note-taking method, data analysis methods and techniques using the agih method with basic techniques for direct elements, while the methods and techniques for presenting the results of data analysis are formal methods with descriptive techniques. The results of this study include the structure of sentences in the dialogue of the film Hafalan Shalat Delisa which is divided into two groups, namely the structure of single sentences and compound sentences. The single sentence structure consists of eight sentence patterns, namely (1) SP, (2) SPO, (3) SPK, (4) SP-Pel, (5) SPOK, (6) SPO-Pel, (7) PK, and (8) PO. In compound sentences there are five sentence patterns, namely (1) SP+SP, (2) SP+PO, (3) SP+PK, (4) Konj+SPO+KSP and (5) SPPel+SPO. The types of sentences in the film dialogue Hafalan Shalat Delisa are divided into three types, namely (a) types of sentences based on the number of clauses, namely single sentences, equivalent compound sentences, multilevel compound sentences and mixed compound sentences, (b) types of sentences based on syntactic classification in the form of declarative sentences, imperative sentences, interrogative sentences, and exclamatory sentences, and (c) types of sentences based on the completeness of their elements in the form of major sentences and minor sentences.